Clindamycin-Loaded Polyhydroxyalkanoate Nanoparticles for the Treatment of Methicillin-Resistant Staphylococcus aureus-Infected Wounds - Muneeb Ullah; Juho Lee; Nurhasni Hasan; Md. Lukman Hakim; Dongmin Kwak; Hyunwoo Kim; Eunhye Lee; Jeesoo Ahn; Bora Mun; Eun Hee Lee; Yunjin Jung; Jin-Wook Yoo (MDPI AG, 2024)
Background/Objectives: Owing to the growing resistance of methicillin-resistant Staphylococcus aureus (MRSA) to conventional antibiotics, the development of innovative therapeutic strategies for the treatment of MRSA-infected cutaneous wounds poses a significant challenge. Methods: Here, by using polyhydroxyalkanoates (PHA), emerging biodegradable and biocompatible polymers naturally produced by various microorganisms, we developed clindamycin-loaded PHA nanoparticles (Cly-PHA NPs) as a novel approach for the treatment of MRSA-infected cutaneous wounds. Results: Cly-PHA NPs were characterized in terms of mean particle size (216.2 ± 38.9 nm), polydispersity index (0.093 ± 0.03), zeta potential (11.3 ± 0.5 mV), and drug loading (6.76 ± 0.19%). Owing to the sustained release of clindamycin over 2 days provided by the PHA, Cly-PHA NPs exhibited potent antibacterial effects against MRSA. Furthermore, Cly-PHA NPs significantly facilitated wound healing in a mouse model of MRSA-infected full-thickness wounds by effectively eradicating MRSA from the wound bed. Conclusions: Therefore, our results suggest that Cly-PHA NPs offer a promising approach for combating MRSA infections and accelerating cutaneous wound healing.